How can we realise the full potential of health systems for nutrition? - Heidkamp, Rebecca A.; Wilson, Emily; Menon, Purnima; Kuo, Helen; Walton, Shelley (BMJ, 2020)
Poor nutrition contributes substantially to global disease, diminishing the wellbeing of women and children in low and middle income countries, and better nutrition must be part of the universal health coverage agenda, say Rebecca Heidkamp and colleagues.